Artificial Intelligence in Education: Opportunities and Challenges - Dini Siamika Tito Prayogi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The rapid development of Artificial Intelligence (AI) has brought significant changes to global educational systems. This technology influences not only learning processes but also pedagogical practices, assessment systems, educational management, and policy formulation. This article aims to examine the opportunities and challenges of Artificial Intelligence in education through a conceptual and literature-based approach. The study employs a critical literature review of peer-reviewed journal articles, academic books, and international policy reports related to AI in educational contexts. The findings indicate that AI offers several strategic opportunities, including personalized learning, enhanced assessment effectiveness, data-driven decision-making, and improved educational governance and quality assurance. However, the implementation of AI in education also presents substantial challenges, such as ethical and data privacy concerns, algorithmic bias, teacher readiness, infrastructural inequality, and weak policy and governance frameworks. This article argues that Artificial Intelligence should not be regarded as a neutral technological solution, but rather as a socio-technical phenomenon that requires careful pedagogical, ethical, and policy considerations. When governed responsibly, AI has the potential to support the development of inclusive, adaptive, and human-centered educational systems.